2013
DOI: 10.1097/aog.0b013e3182883a34
|View full text |Cite
|
Sign up to set email alerts
|

2012 Updated Consensus Guidelines for the Management of Abnormal Cervical Cancer Screening Tests and Cancer Precursors

Abstract: A group of 47 experts representing 23 professional societies, national and international health organizations, and federal agencies met in Bethesda, MD, September 14-15, 2012, to revise the 2006 American Society for Colposcopy and Cervical Pathology Consensus Guidelines. The group's goal was to provide revised evidence-based consensus guidelines for managing women with abnormal cervical cancer screening tests, cervical intraepithelial neoplasia (CIN) and adenocarcinoma in situ (AIS) following adoption of cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
477
0
19

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 668 publications
(525 citation statements)
references
References 100 publications
13
477
0
19
Order By: Relevance
“…In prospective studies, HPV16/18 positivity is linked with a higher risk of future high-grade cervical lesions (Khan et al, 2005;Bulk et al, 2007;Persson et al, 2015). Based on evidence in the research literature, ASCCP guidelines recommend that women aged 30 years or older with normal cytology but positive HPV16/18 should be referred for immediate colposcopy, because they are at particularly high risk of current or future high-grade cervical lesions (Massad et al, 2013). In this study, we have confirmed the triage value of HPV16/18 genotyping in LSIL/CIN1, which is comparable and complementary to earlier published data.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In prospective studies, HPV16/18 positivity is linked with a higher risk of future high-grade cervical lesions (Khan et al, 2005;Bulk et al, 2007;Persson et al, 2015). Based on evidence in the research literature, ASCCP guidelines recommend that women aged 30 years or older with normal cytology but positive HPV16/18 should be referred for immediate colposcopy, because they are at particularly high risk of current or future high-grade cervical lesions (Massad et al, 2013). In this study, we have confirmed the triage value of HPV16/18 genotyping in LSIL/CIN1, which is comparable and complementary to earlier published data.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high spontaneous regression rate among this age group, HPV testing is not recommended (Davey et al, 2014). Similarly, colposcopy associated with HPV16/18 is restricted to women aged 30 years or older (Massad et al, 2013). HPV16/18 genotyping showed no triage value under age of 30 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations